2005
DOI: 10.1038/sj.bjp.0706003
|View full text |Cite
|
Sign up to set email alerts
|

Role of SKCa and IKCa in endothelium‐dependent hyperpolarizations of the guinea‐pig isolated carotid artery

Abstract: 1 This study was designed to determine whether the endothelium-dependent hyperpolarizations evoked by acetylcholine in guinea-pig carotid artery involve a cytochrome P450 metabolite and whether they are linked to the activation of two distinct populations of endothelial K Ca channels, SK Ca and IK Ca. 2 The membrane potential was recorded in the vascular smooth muscle cells of the guinea-pig isolated carotid artery. All the experiments were performed in the presence of N o -L-nitro arginine (100 mM) and indome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
60
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 49 publications
(80 reference statements)
8
60
0
Order By: Relevance
“…20,30,39) At present, the best strategy for blocking EDHF signaling is the combined inhibition of small-and intermediate-conductance K Ca channels. 26,39,42) In the present study, we found that NAd-induced contraction in the presence of NOS inhibition was further amplified by additional co-treatment with inhibitors of small-and intermediate-conductance K Ca channels (apamin and TRAM-34, respectively) and this effect was greater in WKY rats than in SHR. Additionally, ACh-induced EDHF-type relaxation was impaired in the SHR femoral artery.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…20,30,39) At present, the best strategy for blocking EDHF signaling is the combined inhibition of small-and intermediate-conductance K Ca channels. 26,39,42) In the present study, we found that NAd-induced contraction in the presence of NOS inhibition was further amplified by additional co-treatment with inhibitors of small-and intermediate-conductance K Ca channels (apamin and TRAM-34, respectively) and this effect was greater in WKY rats than in SHR. Additionally, ACh-induced EDHF-type relaxation was impaired in the SHR femoral artery.…”
Section: Discussionsupporting
confidence: 49%
“…In addition to NO, EDHF plays an important role in the regulation of vascular tone. 20,39,42) Alterations in K + flux in both smooth muscle cells and endothelial cells are important in EDHF signaling; however, the precise mechanisms remain unclear because the signaling differs by vessel type, species, and disease state. 20,30,39) At present, the best strategy for blocking EDHF signaling is the combined inhibition of small-and intermediate-conductance K Ca channels.…”
Section: Discussionmentioning
confidence: 99%
“…Although the identification of EDHF remains under debate, K + , which effluxes from the endothelial cells through the Ca 2+ -activated K + channels (especially IK Ca and SK Ca channels) has been suggested as a proposed candidate of EDHF. Consistent to other studies [4] , we demonstrated that the EDHF-mediated relaxation could be abolished when the Ca 2+ -activated K + channels were blocked by apamin and charybdotoxin [17] . Indeed, the vasorelaxant effect of K + has been found for over 70 years [18] .…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, 1-[(2-chlorophenyl)diphenylmethyl]-1H-pyrazole (TRAM-34), a specific inhibitor of IK Ca channels, has been used in combination with apamin to confirm that IK Ca and SK Ca channels are involved in EDHFmediated vasodilation. The combination of TRAM-34 and apamin has been used to block EDHF responses in rat caudal [5], saphenous [6], middle cerebral [7] and mesenteric arteries [8] and guinea pig carotid arteries [9].…”
Section: Introductionmentioning
confidence: 99%